Analysis of the Top-Up System in E-Wallet Transactions from the Perspective of Sharia Economic Law - Tesnawati, Eriz; Muthoifin, M (Universitas Muhammadiyah Surakarta, 2025)
The rapid growth of financial technology has reshaped payment systems, particularly through the extensive use of electronic wallets and their top-up mechanisms. This study aims to analyze the e-wallet top-up framework from the perspective of Sharia Economic Law by examining its contractual structure, legal compliance, and potential Sharia-related issues. The analysis is grounded in fiqh muamalah, emphasizing core principles such as the permissibility of transactions (al-ashlu fil mu‘amalat al-ibahah), contractual clarity, and the prohibition of riba, gharar, and maysir. This research employs a qualitative juridical-normative approach supported by comprehensive library research. Primary data consist of Sharia fatwas, statutory regulations, and classical as well as contemporary Islamic economic literature, while secondary data include academic studies on fintech and Sharia compliance. Data are analyzed descriptively and analytically to assess the conformity of e-wallet top-up practices with Sharia principles, particularly referring to DSN-MUI Fatwa No. 116/DSN-MUI/IX/2017 and relevant Bank Indonesia regulations. The findings indicate that e-wallet top-up systems generally involve multiple contractual arrangements, with qardh functioning as the dominant contract, as user funds are treated as loans to e-wallet providers. Although the mechanism is fundamentally permissible, potential Sharia concerns arise from promotional incentives such as cashback that may lead to riba al-qardh, as well as refund delays that could create gharar. Nonetheless, Sharia-compliant e-wallets that place funds in Islamic banks, ensure real-time taqabudh, and operate under Sharia Supervisory Board oversight largely comply with Sharia requirements. The originality of this study lies in its comprehensive examination of the top-up mechanism as a complex Sharia contractual structure, offering normative legal recommendations to strengthen Sharia compliance in digital payment systems.